The Complementary Therapy in Nursing: Bridging the Physical and Mental Health of Patients - baharuddin, baharuddin (ASIAN PUBLISHER, 2023)
Complementary therapy has gained increasing popularity in modern nursing practice as a non-pharmacological approach to enhance the physical and mental health of patients. This systematic review aims to explore the effectiveness of complementary therapies in bridging the gap between the physical and mental well-being of patients. The review includes various studies encompassing a wide range of complementary therapies, such as aromatherapy massage, tai chi qigong, qigong exercise, acupuncture, music therapy, foot reflexology massage, therapeutic touch, and warm compress therapy. Complementary therapy plays a significant role in nursing care by bridging the gap between the physical and mental health of patients. Various studies have consistently shown the positive effects of complementary therapies on different aspects of patient well-being. Aromatherapy massage improves sleep quality and reduces psychological distress, while tai chi qigong enhances psychosocial well-being and reduces fatigue symptoms among cancer survivors. Qigong exercise programs alleviate depression levels in elderly individuals, and acupuncture effectively reduces cancer pain. Music therapy positively impacts the physical and mental well-being of patients undergoing cardiovascular surgery, and therapies such as aromatherapy, foot reflexology massage, and therapeutic touch provide relief from agitation, anxiety, and pain in patients with dementia, breast and lung cancer, and cardiac catheterization, respectively. Additionally, studies conducted in Indonesia highlight the effectiveness of complementary therapies in reducing preoperative anxiety, pain during labor, and improving sleep quality in breast cancer patients, as well as enhancing social skills and communication in children with autism. The utilization of complementary therapies in nursing care promotes holistic patient-centered approaches and optimizes patient outcomes by addressing the physical and mental dimensions of health.